2018
DOI: 10.15171/apb.2018.064
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Peptide Nucleic Acids in Future Therapeutic Applications

Abstract: Peptide nucleic acids (PNA) are synthetic analog of DNA with a repeating N-(2-aminoethyl)-glycine peptide backbone connected to purine and pyrimidine nucleobases via a linker. Considering the unique properties of PNA, including resistance to enzymatic digestion, higher biostability combined with great hybridization affinity toward DNA and RNA, it has attracted great attention toward PNA- based technology as a promising approach for gene alteration. However, an important challenge in utilizing PNA is poor intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 78 publications
(62 reference statements)
0
51
0
Order By: Relevance
“…Since PNA is not negatively charged, there is no electrostatic repulsion between DNA and RNA, PNA is more effective than ODN in binding to the mRNA of a target gene. 21 Against this background, we designed an anti-CITED1-PNA that was complementary to the first 10 codons of the open reading frame of CITED1 mRNA. This probe stimulates degradation of CITED1 mRNA and inhibits further protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PNA is not negatively charged, there is no electrostatic repulsion between DNA and RNA, PNA is more effective than ODN in binding to the mRNA of a target gene. 21 Against this background, we designed an anti-CITED1-PNA that was complementary to the first 10 codons of the open reading frame of CITED1 mRNA. This probe stimulates degradation of CITED1 mRNA and inhibits further protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…20 Considering the unique properties of PNA, including resistance to enzymatic digestion, inhibition of gene expression of interest appears to be an effective method of cancer treatment. 21 Different from 99m Tc, 177 Lu is a long half-life (6.7d) nuclide that can simultaneously emit β-particles and γ-rays for targeted radionuclide therapy (TRT) and single-photon emission computed tomography (SPECT). 22 For patients who are not susceptible to conventional 131-iodine therapy or who have distant metastases, 177 Lu may constitute a good alternative nuclide for the treatment of iodine-insensitive PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Another way of targeting DNA and RNA moieties is by using peptide nucleic acids (PNA). These are synthetic analogues of DNA that are highly stable and have a hybridization affinity toward natural DNA and RNA, and are therefore a potential approach for the modification of gene expression and epigenetic states 176 . This approach has been applied to the targeting of the lncRNA HOTAIR to block its interaction with EZH2, resulting in reduced invasiveness and increased sensitivity to chemotherapy 177 .…”
Section: Translational Relevance Of Csc Epigeneticsmentioning
confidence: 99%
“…Because the pattern of mRNA expression varies with protein content and researchers found that RNA may have function without translation to the protein, 23 we also measured expression of survivin and phosphorylated survivin on Thr34 (p-survivin) in PBMCs by western blot analysis. Therefore, although, analyses showed similar expression patterns of survivin in PBMCs of BD patients We next classified patients into two groups: patients with active disease and patients with inactive disease.…”
Section: Birc5 Gene Is Overexpressed In Pbmcs In Bdmentioning
confidence: 99%